A randomized phase III trial of adjunctive zonisamide in pediatric patients with partial epilepsy. Issue 8 (9th July 2013) - Guerrini, Renzo; Rosati, Anna; Segieth, Joanna; Pellacani, Simona; Bradshaw, Kate; Giorgi, Luigi
Summary Purpose To assess the efficacy and safety/tolerability of adjunctive zonisamide treatment in pediatric patients with partial epilepsy. Methods In this phase III, double‐blind, randomized, placebo‐controlled, multicenter trial, 207 patients (age 6–17 years) with partial epilepsy, receiving one or two antiepileptic drugs, were randomized to receive adjunctive zonisamide or placebo. Zonisamide was initiated at 1 mg/kg/day, titrated to a target dose of 8 mg/kg/day over 8 weeks (one down‐titration permitted), and maintained for 12 weeks. The primary efficacy end point was the proportion of responders (≥50% seizure frequency reduction from baseline) during the 12‐week maintenance period. Safety/tolerability assessments included the incidence of treatment‐emergent adverse events (TEAEs). Key Findings In total, 93 (86.9%) of 107 patients randomized to zonisamide and 90 (90.0%) of 100 patients randomized to placebo completed the trial. Responder rates were 50% for zonisamide versus 31% for placebo (p = 0.0044; intention‐to‐treat population, last observation carried forward). The overall incidence of TEAEs was similar for zonisamide (55.1%) versus placebo (50.0%), with low rates of serious TEAEs with zonisamide and placebo (3.7% vs. 2.0%) and TEAEs leading to withdrawal (0.9% vs. 3.0%). TEAEs reported more frequently with zonisamide versus placebo were decreased appetite (6.5% vs. 4.0%), decreased weight (4.7% vs. 3.0%), somnolence (4.7% vs. 2.0%), vomiting (3.7% vs. 2.0%), and diarrhea (3.7% vs. 1.0%). Significance Adjunctive zonisamide treatment was shown to be effective and well tolerated in pediatric patients with partial epilepsy. No new or unexpected safety findings emerged.